Experimental and applied modeling of unsaturated soils : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Hoyos, Laureano R., 1972-; Zhang, Xiong, 1971-; Puppala, Anand J. (American Society of Civil Engineers, 2010)
Proceedings of sessions of GeoShanghai 2010, held in Shanghai, China, June 3-5, 2010. Hosted by Tongji University, China; Shanghai Society of Civil Engineering, China; Chinese Institution of Soil Mechanics and Geotechnical Engineering, China. In cooperation with Alaska University Transportation Center, USA; Geo-Institute of ASCE, USA; Deep Foundation Institute, USA; East China Architectural Design and Research Institute Company, China; Georgia Institute of Technology, USA; Nagoya Institute of Technology, Japan; Transportation Research Board, USA; University of Newcastle, Australia; University of Illinois at Urbana-Champaign, USA; University of Kansas, USA; University of Tennessee, USA; Vienna University of Natural Resources and Applied Life Sciences, Austria. This Geotechnical Special Publication contains 28 papers examining the most current thinking and practices involving unsaturated soils. Geotechnical and civil engineers all over the world face problems with a wide range of geosystems involving materials that remain under partially saturated conditions throughout the year. The lack of education and training among engineering graduates and practitioners to deal properly with unsaturated soil conditions has resulted in faulty or excessively conservative designs, frequent construction delays, and deficient long-term performance of built infrastructure. Over the last few decades, however, the discipline of unsaturated soil mechanics has begun to receive increasing attention worldwide, providing better explanations for soil behavioral patterns than conventional saturated soil mechanics. Papers in this proceedings address, first, general characterization and constitutive behavior, and second, applied modeling and analysis.
Keywords: Soil mechanics -- Simulation methods -- Congresses.; Zone of aeration -- Simulation methods -- Congresses.; Soil moisture -- Measurement -- Congresses.; elektronické knihy; electronic books